Collaborative archiving of music and dance : framework for a more-inclusive postcolonial archive among contemporary Bagisu, Uganda - Makwa, Dominic D.B. (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.